1996
DOI: 10.1159/000177127
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Gender-Related Differences in Success, Major and Minor Complication Rates and the Duration of Hospitalization after Percutaneous Transluminal Coronary Angioplasty

Abstract: This report describes the effect of age and gender on the results of balloon angioplasty using current technique and indications. A consecutive group of 2,067 patients who underwent angioplasty at a single institution after 1990 is described. Angioplastic success was 92.2% and similar among men and women and the various age groups. Sixteen patients (0.8%) died, and mortality among women was significantly higher (1.4 vs. 0.6%, p < 0.001). There were no age or gender differences in the rate of Q-wave myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The observations from this study are in agreement with previous reports on sex-related differences in clinical characteristics of patients treated with PCI [1][2][3][4][5][6][7][8][9]. The main findings regarding the outcome after SES implantation in women as compared with men may be summarized as follows: use of SES in real-world patients was associated with high acute clinical and procedural success in both sexes; PCI complexity, and percentage of multiple stent implantation did not differ between sex; when treated with SES, women and men had low and similar 6-month MACE rate; sex, per se, has not to be considered a predictor of MACE after SES on long-term (> 2 years) follow-up [10].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The observations from this study are in agreement with previous reports on sex-related differences in clinical characteristics of patients treated with PCI [1][2][3][4][5][6][7][8][9]. The main findings regarding the outcome after SES implantation in women as compared with men may be summarized as follows: use of SES in real-world patients was associated with high acute clinical and procedural success in both sexes; PCI complexity, and percentage of multiple stent implantation did not differ between sex; when treated with SES, women and men had low and similar 6-month MACE rate; sex, per se, has not to be considered a predictor of MACE after SES on long-term (> 2 years) follow-up [10].…”
Section: Discussionsupporting
confidence: 93%
“…These observations were extensively reported in the bare-metal stent era and were believed to be related to higher frequency of acute coronary syndrome at presentation, higher risk profile, and smaller coronary vessels [1][2][3][4][5][6][7][8][9]. The widespread use of drugeluting stents has contributed to a more aggressive percutaneous treatment of coronary disease even in unfavorable clinical and anatomical settings such as diabetes, long lesions, bifurcation lesions, and small vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Various research publications and registry data previously reported higher rates of mortality in women following angioplasty. [14][15][16][17] The women in the study by Timaran et al 18 had significantly poorer rates of primary patency and were at increased risk for intervention than the men in the study. Additionally, Rosenman et al 15 reported higher rates of minor complications and lengths of hospitalization in female patients.…”
Section: Discussionmentioning
confidence: 82%
“…These collective findings have been attributed to the smaller body habitus typically seen in female patients. 15,17 Therefore, for a given amount of atherosclerotic disease, this may be associated with a greater cross-sectional area reduction in females, which subsequently manifests as worse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the practical considerations with this device is the need in certain instances for a larger sheath than other balloon-expandable stents on the market (configurations are compatible with either 7-F or 8-F introducer sheaths). Historically, access site complication rates have been 10.5% for women and 5% for men, 34 but in modern interventions it has been shown that closure devices are a negative predictor for access site complications. 35 A major access site-related complication rate of ~2% to 3% has been frequently reported, 36,37 which is acceptable according to the Society of Interventional Radiology quality improvement guidelines.…”
Section: Discussionmentioning
confidence: 99%